THE DEVELOPMENT OF AN INTEGRATED DANCE LEARNING MANAGEMENT MODEL USING MICRO LEARNING TO PROMOTE CRITICAL THINKING SKILL IN 21st CENTURY FOR STUDENTS IN GRADE 5, WIENGSA SCHOOL, SURATTHANI PROVINCE - Tueksuban, Suchaya (Journal of MCU Nakhondhat, 2024)
This article of this study was: 1) Study the current situation, problems and needs of dance learning management, 2) Create and develop a dance learning management model, 3) Experiment with dance learning management model, and 4) Evaluation of an integrated dance management model using micro learning to promote critical thinking skills in 21st century for student in grade 5, Wieng sa School, Suratthani Province. This was integrated research design for mixed method is divided into 2 steps: quantitative using questionnaires, sample group includes: M. 5/3, 5/4 of 90 peoples. By using for analyzed percentage, mean, standard deviation. And qualitative In-depth interviews by purposive sampling were key informants such as: 1) Executives, 2) Dance teachers, 3) Academics, and 4) Students of 12 peoples. By analyzing the content and summarizing. The research was found that: 1) The current situation the situation is moderate ( = 3.66, S.D. = 0.43), problems overall situation is moderate ( = 3.41, S.D. = 0.75), and needs the high level ( = 4.46, S.D. = 0.56), 2) The results of the creation and development of dance learning management model, the overall evaluation results are at the highest level ( = 4.59, S.D. = 0.49), 3) The experimental result model showed that the experimental group was higher than the control group ( 2 = 35.70, S.D. = 4.54), ( 2 = 21.57, S.D. = 4.28), Integrated thinking ( 2 = .88, S.D. = 4.79), ( 2 = 24.24, S.D. = 4.30), Practical skills ( 2 = 36.76, S.D. = 4.60), ( 2 = 29.64, S.D. = 4.44), and 4. The evaluation results of the use of learning management formats were found to be appropriate in terms of format, steps, processes, feasibility, correctness, comprehensiveness, and usefulness at the highest level ( = 4.59, S.D.= 0.67)